(untitled) (Marketing Journal, 2025)
This article is a comprehensive statistical analysis of farm performance research, focusing on statistical indicators of farm performance. The article discusses various 48 statistical methods — descriptive statistics, correlation, regression analysis, and time series analysis — to study regional disparities, resource allocation, technological adoption, and the impact of climate variability on farm output. Economic implicatio ns and the need for regional cooperation to increase the importance of farms in agriculture are also discussed.